(untitled) (Agricultural Engineering, 2017)
The study evaluates granulated coffee grounds use as an additive to soil. Specific physico-chemical and functional properties of soil that enable assessment of its fertility and that have a possible impact on plants growth and development were analysed. The research proved that granulated coffee grounds added to soil increase sorption properties and decrease pH of the soil solution. Moreover, the increase of the phenol compounds that decreased the germination ability and reduced the length of roots of a test plant, namely winter wheat, was reported.